Assessment of Antibacterial and Anti-biofilm Effects of Vitamin C Against Pseudomonas aeruginosa Clinical Isolates - Abdelraheem, Wedad M.; Refaie, Marwa M. M.; Yousef, Rehab Kamal Mohamed; Abd El Fatah, Aliaa S.; Mousa, Yosra M.; Rashwan, Rabab (Frontiers in Microbiology, 2022)
There is a growing need to look at alternative therapeutic modalities to help control the pandemic of antimicrobial resistance. In vitro and in vivo assessment of antibacterial and anti-biofilm effects of vitamin C (ascorbic acid) is the aim of the current study. The micro-dilution method determined the minimal inhibitory concentration (MIC) of ascorbic acid or antibiotics alone and in combinations against P. aeruginosa clinical isolates. The micro-titer plate method monitored the effect of ascorbic acid on the biofilm-forming isolates of P. aeruginosa. The effect of ascorbic acid on the differential expression of different antibiotic-resistant genes and biofilm encoding genes of P. aeruginosa isolates were also tested using real-time PCR. For in vivo assessment of the antibacterial and anti-biofilm effects of ascorbic acid alone or combined with an antibiotic, the rats were infected with P. aeruginosa clinical isolate followed by different treatment regimens. MICs of ascorbic acid among P. aeruginosa isolates were156.2-1250 µg/ml, with MIC50 and MIC90 were 312.5 and 625μg/ml, respectively. At sub-inhibitory concentrations (19.5-312.5 µg/ml), ascorbic acid had 100% biofilm inhibitory effect. Furthermore, ascorbic acid treated bacteria showed down regulation of genes underpinning biofilm formation and antibiotic resistance. In vivo assessment of vitamin C and ceftazidime in rats showed that administration of both at a lower dose for treatment of pseudomonas infection in rats has a synergistic and more powerful effect. Conclusion: Vitamin C shows excellent in vitro results as an antibacterial and anti-biofilm agent. Vitamin C should be routinely prescribed with antibiotics to treat bacterial infections in the clinical setting.